Differentiating Mobile Masses on Transcatheter Aortic Valve: Thrombi or Vegetations? - Alexander Arreguin; Akash Goyal; Konstantinos Dean Boudoulas; Adam Potter; Timothy Obarski (Case Reports in Cardiology)
A 58-year-old female presented with new-onset dyspnea. Two years prior, she had undergone a transcatheter aortic valve replacement with a 26-mm Edwards Sapien 3 valve. Diagnostic testing included transthoracic and transesophageal echocardiograms that revealed increased transvalvular gradients and suspected prosthetic thrombosis. Laboratory testing included blood cultures that unexpectedly grew Streptococcus sanguinis. This case highlights the difficulty in differentiating prosthetic valve thrombosis from infective endocarditis and the possible therapeutic complications that could arise.